Rotary Switched Reluctance Actuator: A Review on Design Optimization and Its Control Methods - Siau Ping Tee; Mariam Md Ghazaly; Shin Horng Chong; Irma Wani Jamaludin (Institute of Advanced Engineering and Science, 2017)
A switched reluctance actuator (SRA) is a type of electromagnetic stepper actuator that is gaining popularity for its simple and rugged construction, ability of extremely high-speed operation and hazard-free operation. SRA gained supremacy over permanent magnet actuators due to the fact that its building material are relatively low cost compared to the expensive and rare permanent magnets. SRA is already making its debut in automotive, medical and high precision applications. However, many parties are still oblivious to this new age actuator. This paper reviews the latest literature in terms of journal articles and conference proceedings regarding the different design parameters and control method of SRA. The impact of the parameters on the performance of SRA are discussed in details to provide valuable insight. This paper also discussed the advantages of various novel SRA structure designs that prove to be a huge contribution to the future technology. It is found that several design parameters such as the air gap when kept minimum, increases torque value; while increasing number of phases in SRA minimizes torque ripples. Increased stator and rotor arc angles will increase torque, not to mention a larger excitation current can also achieve the same effect. Researches are often done through Finite Element Method (FEM) analysis to verify the optimized design parameters before fabrication, whilst experimental procedures are executed to verify the simulation results. To ensure smooth phase switching and improved torque output, intelligent controllers are employed in speed control and direct torque control (DTC) methods of SRA.